2017
DOI: 10.18632/oncotarget.17412
|View full text |Cite
|
Sign up to set email alerts
|

Targeted next generation sequencing identifies somatic mutations and gene fusions in papillary thyroid carcinoma

Abstract: 138 papillary thyroid carcinoma (PTC) samples were assessed for somatic mutation profile and fusion genes by targeted resequencing using a cancer panel (ThyGenCapTM) targeting 244 cancer-related genes and 20 potential fusion genes. At least one genetic alteration (including mutations and fusion genes) was observed in 118/138 (85.5%) samples. The most frequently mutated gene was BRAF V600E (57.2%). Moreover, we identified 11 fusion genes including eight previously reported ones and three novel fusion genes, UEV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…In 2016, our group also described the mutational profile of 77 Korean patients with cPTC based on an RNA-seq analysis [6]. In our study cohort, 71.43% of cPTC patients harbored BRAF V600E , which is a slightly higher rate than has been reported in other studies [417181920]. An NRAS mutation was only found in 1.3% of study subjects, whereas 18.18% of cases of cPTC had gene rearrangements in RET (5.18%), BRAF (3.9%), NTRK1/3 (3.9%), ALK (1.3%), FGFR2 (1.3%), and THADA (1.3%).…”
Section: Genomic Characteristics Of Classical Ptcmentioning
confidence: 66%
See 1 more Smart Citation
“…In 2016, our group also described the mutational profile of 77 Korean patients with cPTC based on an RNA-seq analysis [6]. In our study cohort, 71.43% of cPTC patients harbored BRAF V600E , which is a slightly higher rate than has been reported in other studies [417181920]. An NRAS mutation was only found in 1.3% of study subjects, whereas 18.18% of cases of cPTC had gene rearrangements in RET (5.18%), BRAF (3.9%), NTRK1/3 (3.9%), ALK (1.3%), FGFR2 (1.3%), and THADA (1.3%).…”
Section: Genomic Characteristics Of Classical Ptcmentioning
confidence: 66%
“…Another frequently altered gene, G protein-coupled receptor LPAR4 (2.7%), was also discovered, and the malignant transformation of PTC through LPAR4 mutation was revealed. In 2017, another Chinese PTC cohort with 138 patients was analyzed using the targeted sequencing method [ 19 ]. This study displayed a similar incidence of BRAF V600E (57.25%) as the TCGA cohort, whereas only 2.17% of tumors harbored a RAS mutation ( KRAS only).…”
Section: Genomic Characteristics Of Classical Ptcmentioning
confidence: 99%
“…As with other tyrosine kinases, the oncogenic fusion mechanism consists of juxtaposing of the 3ā€² region of RET gene with the 5ā€² region of a partner gene resulting in a constitutive and ligand independent receptor activation 69,70 . RET fusions have been reported in 4.4% 71 to 6.8% 72 of papillary thyroid carcinomas, especially in populations exposed to radiation, 73 in 1% to 3% of nonā€small cell lung carcinomas and in 0.2% to 1.6% of colorectal carcinomas 74,75 …”
Section: Ret Fusion Uterine Sarcomamentioning
confidence: 99%
“…Moreover, we found a 5% allele frequency of BRAF mutation; such a low value may be explained because of other non-neoplastic cells commixed with neoplastic ones (i.e., lymphocytes, stromal cells), highlighting the clinical relevance of using a high-sensitivity technique, such as next-generation sequencing (tumoural cell content of specimens tested: 20%). Recently, some authors identified a genetic alteration of the MAPK (Mitogen-Activating Protein Kinase) pathway in about 70% of PTC using NGS, detecting either point mutations or structural rearrangements [20]. This technique allowed the recognition of other novel molecular alteration in PTC, as in our case [21].…”
Section: Discussionmentioning
confidence: 83%